Design and Build a Rugby Ball Thrower in the Kontes Robot ABU Indonesia 2020 Using Pneumatic - Imran, Ali; Sapto Aji, Wahyu (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
The Kontes Robot ABU Indonesia (KRAI) is a robot contest held by the Directorate General of Higher Education (DIRJEN DIKTI). The winner of the national robot contest then represented Indonesia at the ABU (Asia–Pacific Broadcasting Union) Robocon which in 2020 was held in Fiji. Robot competition consists of two kinds, namely manual robots and automatic robots. In the competition there is one session or section, namely throwing the rugby ball. In the rugby ball throwing session, it is expected that the ball can be thrown and right into the goal so that it gets a maximum point of 5 points. This study tested the throw using pneumatics with the aim of getting the throw to get 5 points. The parameter that must be achieved is mechanical optimization with the throw landing on target and into the goal so as to get maximum points. The KRAI 2020 robot thrower uses pneumatics. Wind pressure determines the strength of a rugby ball toss. In calculating the distance, the parabolic formula is used and the method used to retrieve data through trial and error is to experiment from two angles, namely 40, and 50 then take good data.